Climate Action and the Impact of Heat Stress on Poultry Production in Fiji - Igbal, Mohammed Rasheed; Iqbaal, Ubaadah Bin; Kumar, Shaista Snehal; Magiri, Royford Bundi; Kumar, Saleshni (Journal of Ecohumanism, 2024)
One of the significant reasons for monetary misfortunes in the animal market is climate change, including high ambient temperature or Heat Stress. The poultry industry is an essential aspect of the livestock market. Yet, it faces adverse losses due to heat stress. An increment within the natural temperature is unfavorable for the livestock market worldwide, thus, affecting the poultry industry. The meat derived from poultry sustains a low number of saturated fatty acids and contains many vitamins, minerals, and proteins. Likewise, poultry eggs are the most available source of animal protein. However, heat stress leads to numerous changes in the physiology of the chicken body, such as immunological responses and oxidative stress, resulting in mortality, reduced feed efficiency, feed intake, and many more. Heat stress also affects the process and production of eggs and their quality on laying hens while reducing the growth rate in broilers. Thereby, strategies with a degree of effectiveness have been established to mitigate heat stress in poultry. Nutritional techniques like dual feeding, wet feeding, restrictions in the feed time, vitamins, minerals and electrolytes, and proper ventilation area with adequate housing and environment have been found to minimize the devastating effects of heat stress.